The Grain Corporation and the Guaranteed Wheat Price - Eldred, Wilfred (Quarterly Journal of Economics, 1920)
Events of 1917: the Food Control Act, the guaranteed price, the "fair" price, 698. — The operations of the Grain Corporation in 1917–18, 699. — The guarantee extended to 1919, 704. — The Price Guarantee Act of March 4, 1919, 707. — Crop and prices of 1919, 708. — Expiration of the guarantee; plans for resumption of future trading, 715. — Relative advance in prices of wheat, flour, and bread since 1913, 717. — Financial outcome of the Grain Corporation's activities, 718.